Integration of GIS and Hierarchical Multi-Criteria Analysis for Mapping Flood Vulnerability: The Case Study of M’sila, Algeria - Loumi, K.; Redjem, A. (Engineering, Technology & Applied Science Research, 2021)
This paper proposes the integration of GIS (Geographic Information System ) and HMA (Hierarchical Multi-criterion Analysis) offering a low-cost methodology to produce vulnerability maps. The quintessential role the rivers play in urban development has long been asserted and accepted. However, one of the subsequent consequences of these urban development activities is the increased frequency of floods. The case in point is the city of M’sila, Algeria. The subject city was settled along the banks of a river known as Oued El Ksob, which undoubtedly had a significant influence on its development. In the last 50 years, M’sila has experienced significant spatial growth, especially in its north and northwest sides. As such, the work presented in this article aims to assess the vulnerability of the city to the risks of flooding. The approach used is based on the combined use of the HMA method coupled with the GIS. The process allowed the graphical representation of the resulting analysis of complex data of the territory, i.e. the mapping of its vulnerability to flooding. The map has four vulnerability categories ranging from low to very strong. The proposed system serves as an essential decision-making tool for local government officials.